2018
DOI: 10.1002/ejhf.1342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sacubitril/valsartan on neprilysin targets and the metabolism of natriuretic peptides in chronic heart failure: a mechanistic clinical study

Abstract: Aim This study aimed at evaluating the effects of sacubitril/valsartan on neprilysin (NEP), and the metabolism of natriuretic peptides in heart failure (HF) and providing additional mechanistic information on the mode of action of the drug. Methods and results We enrolled 73 chronic HF patients who were switched from angiotensin‐converting enzyme inhibitor or angiotensin receptor blocker to sacubitril/valsartan. In addition to clinical and echocardiographic assessment, plasma biomarkers were measured at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
129
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(143 citation statements)
references
References 25 publications
2
129
2
3
Order By: Relevance
“…Furthermore, within this data set, TD was linked to responder status, further supporting efforts to achieve maximum dose. Our data, while not reporting on clinical end points, indicate a similar community response in terms of natriuretic peptide and ST2 reduction, to that observed in PARADIGM‐HF, and extend the clinical trial observations by demonstrating an increase in LVEF over time with this therapy . We also noted that those responding to therapy tended to be younger and had better renal function.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Furthermore, within this data set, TD was linked to responder status, further supporting efforts to achieve maximum dose. Our data, while not reporting on clinical end points, indicate a similar community response in terms of natriuretic peptide and ST2 reduction, to that observed in PARADIGM‐HF, and extend the clinical trial observations by demonstrating an increase in LVEF over time with this therapy . We also noted that those responding to therapy tended to be younger and had better renal function.…”
Section: Discussionsupporting
confidence: 81%
“…The clinical importance of these data is that they reinforce the positive observations from the clinical trial data, and the emerging real world data, and indicate that the majority of the cohort of community patients can tolerate the agent and benefit from the compound, in terms of either a reduction in NT‐proBNP or an improvement in LVEF. More importantly, these data support the importance of achieving maximum dose and link this to a reduction in diuretic use, establishing clinical volume assessment as a critical feature in using this agent.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Finally, it has recently been demonstrated that sacubitril/valsartan increases the levels of glycosylated proBNP, which is especially resistant to cleavage into BNP and NT-proBNP. 10 Therefore, we would expect lower BNP levels under sacubitril/valsartan treatment, 11 although showing cross-reactivity with proBNP, may hide those results.…”
Section: Sacubitril/valsartan and B-type Natriuretic Peptide Value: Rmentioning
confidence: 96%